The Level of Code Switching Employed by English Education Department Students: A Study on Speaking Skill at Proposal Seminar Presentation - Finessa Salsabila; Jufrizal Jufrizal (Universitas Negeri Padang, 2022)
This study aims to analyze the level of code-switching employed by English education students based on how often code-switching employs in proposal seminar discussions. This research also finds out the type of code-switching students employ most often. The researcher observed and analyzed video recordings by students through zoom meeting recordings during the proposal seminar discussion session. The researcher uses descriptive-quantitative to determine and measure the frequency level of how often students use code-switching. The research subjects in this study were English education students who recorded videos starting from the proposal seminar discussion session. The results showed that students who conducted a proposal seminar in April employed code switching during discussion sessions. The most frequently employed types are intra-sentential, inter-sentential, and extra-sentential. The level of student code-switching is at low and very low levels, but students often use Indonesian during the proposal seminar discussion session instead of using English. It shows that the students' speaking ability is still very limited using English.